Application of Physiotherapy to patients with carpal tiinel syndrome and Hemodialysis Programs (Cuestiones de Fisioterapia, 2005)
In the last few years, an increased number of cases of amyloidosis in patients with chronic renal failure having more than 7 or 8 years of hemodialysis treatment has been observed. A plasmatic protein, B2-microglobuline, having an exclusively renal metabolism, tends to build up on the synovial of tensions and joints. The Carpal Tunnel Syndrome is the most frequent pathology found in our unit. These patients suffer motor and sensitive alterations and pain, resulting in decreased functional abilities and rest and self-esteem alterations. Although surgical decompression has a high improvement rate, this treatment is not a definitive one for patients in a hemodialysis program. Improvement in the quality of life of patients with Carpal Tunnel Syndrome in a hemodialysis program is an important objective in physiotherapy treatment. This research project uses observation and questionnaire as essential instruments, along with an assessment protocol. Through the application of an exercise treatment program, physiotherapy objectives have been achieved as follow: Null (1 patient), no improvement (2 patients), mild Improvement (3 patients) and improvement (4 patients).